Application and recent advances in conventional biomarkers for the prognosis of papillary thyroid carcinoma - Li, Muzi; Li, Qiong; Zou, Cancan; Huang, Qin; Chen, Yanlin (Frontiers in Oncology, 2025)
Cancer remains one of the most common and deadliest diseases worldwide. Among endocrine neoplasms, the incidence of thyroid malignancies has been rising in recent years. Papillary thyroid carcinoma (PTC), the most frequently observed histological subtype of thyroid cancer (THCA), typically yields favorable clinical outcomes for affected individuals. However, this has raised concerns about the overdiagnosis and underdetermination of the prognostic factors in PTC cases. As a result, researchers now advocate for patient stratification and tailored therapeutic approaches for PTC cases, with the goal of minimizing unnecessary surgical procedures and radioiodine treatments. These treatments can lead to clinical complications and impose avoidable physiological and psychological stress on patients. Multiple prognostic biomarkers have been identified for PTC, which play a critical role in predicting outcomes and informing treatment decisions. This review examines both established molecular tools and recent advancements in the determination of prognosis in in papillary thyroid carcinoma.